Role of International Cooperation in the Peaceful Settlement of the Conflict in Ukraine (2014-2015) - Mikhail Mikhailovich Shumilov (Управленческое консультирование)
The paper reveals the role of the international community in settling the conflict in eastern Ukraine. The focus is on considering the “Norman Quartet’s” efforts as well as such OSCE instruments as Special Monitoring Mission of international observers and The Trilateral Contact Group on Ukraine. The author clarifies the achieved results, issues and the prospects of the peaceful negotiating process.